Beginning Japanese for Professionals Book 1 - Konomi, Emiko (Open textbook library., 2015)
This textbook is designed for beginning learners who want to learn basic Japanese for the purpose of living and working in Japan. Unlike textbooks written primarily for students, whose content largely centers on student life, this book focuses more on social and professional life beyond school. As a beginning level textbook, this book includes many elementary grammar patterns (Japanese Language Proficiency Test Levels 5 and 4), but the vocabulary and situations are selected specifically for working adults. Explanations are kept concise so as to only cover key points. The main focus is on oral communication and the accompanying audio is to be used extensively. This textbook can be used for self-study, as part of an online course, or as a traditional college course.